Cyclic reaction-induced enhancement in the dehydrogenation performances of the KNH2-doped LiNH2 and LiH system. (30th September 2020) - Ping, Chao; Feng, Bao-Qi; Ge, Jun; Li, Guang-Zhen; Zhu, Wei; Teng, Yun-Lei; Zhang, Ya-Ru; Dong, Bao-Xia
Abstract: Ammonia is a vital intermediate in the hydrogen desorption process of Metal-N-H system. KH has strong reactivity with NH3 to form KNH2 . We speculate that KNH2 is also an intermediate formed during hydrogen desorption of the potassium-doped M-N-H systems. In this research, the dehydrogenation performance of the KNH2 -doped LiNH2 and LiH composition was first studied. Compared with the broad dehydrogenation curve of the composite material of LiNH2 and LiH without the catalyst, the dehydrogenation curve of 0.05 mol KNH2 -doped composite material was significantly narrowed. The initial and peak dehydrogenation temperature of the composite to which 0.05 mol of KNH2 was added was lowered remarkably. Besides, the cyclic dehydrogenation properties of the LiNH2 and LiH system was also significantly enhanced by the introduction of KNH2 . The cyclic conversion of KNH2 to KH is the main reason for the enhancement of the hydrogen evolution performance of the LiNH2 –LiH system doped with KNH2 . We found the KNH2 -doped Li–N–H system exhibits similar dehydrogenation property with that of the KH-doped Li–N–H system. This work proves that KNH2 plays a key role in improving the hydrogen desorption performances of the potassium-doped M-N-H systems. Graphical abstract: Image 1 Highlights: Hydrogen desorption properties of the KNH2 -doped Li–N–H system was examined. Hydrogen desorption kinetics are significantly enhanced by introducing KNH2 . The dehydrogenation temperature is lowered drastically. The improved properties induce from the cyclic conversion from KNH2 to KH. KNH2 may be formed during dehydrogenation of the potassium-doped M-N-H system.